2005
DOI: 10.1007/s00059-005-2659-8
|View full text |Cite
|
Sign up to set email alerts
|

Normal Coronary Arteries: Clinical Implications and Further Classification

Abstract: The term "chest pain with normal coronary arteries" encompasses a large number of different cardiac pathophysiological abnormalities, including impairment of coronary flow reserve, endothelial dysfunction, and early atherosclerosis that, in most cases, cannot be readily differentiated one from the other. To study early coronary atherosclerosis, physicians must look beyond contrast filled arteries (so called lumenology). Angiograms cannot evaluate the vessel wall, plaque distribution and composition or other mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 43 publications
1
10
0
3
Order By: Relevance
“…It is currently recognized that coronary endothelial dysfunction can be detected in some patients with minimally obstructive coronary artery disease and angina [7,8,[17][18][19][20]. Thus, endothelial dysfunction in microvascular angina has been explained as a generalized process that can involve both coronary and peripheral conduit arteries and is similar to that observed in patients with organic atherosclerotic disease [21].…”
Section: Discussionmentioning
confidence: 95%
“…It is currently recognized that coronary endothelial dysfunction can be detected in some patients with minimally obstructive coronary artery disease and angina [7,8,[17][18][19][20]. Thus, endothelial dysfunction in microvascular angina has been explained as a generalized process that can involve both coronary and peripheral conduit arteries and is similar to that observed in patients with organic atherosclerotic disease [21].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies demonstrated that vasomotor dysfunction of epicardial coronary arteries is a predictor of cardiac events in patients without angiographic evidence of CAD [22]. In addition, it was shown that many patients with chest pain and normal vessels at coronary angiography have early atherosclerosis, as documented by intravascular ultrasound, reduced CFR and coronary endothelial dysfunction [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the analysis should always be integrated with coronary angiography and CT scan in order to access the precise location of the LCA origin and the location of its network of collaterals before choosing the appropriate intervention, as in the case reported. [14][15][16][17][18][19][20][21][22] …”
Section: Commentmentioning
confidence: 99%